Real-time/concurrent knowledge - Shariq, Syed Z. (Journal of knowledge management, 2004)
The purpose of this paper is to meet the challenge of modeling knowledge organization by introducing a new, unifying, way of thinking about the organization of knowledge. Building on ideas set forth in the behavioral theory of the firm we present a modeling framework in which the central idea is to represent the organization of knowledge as a structure that defines the flow of information among members with limited levels of cognitive skill. Such a structure is referred to as an architecture. The need to design architectures that help their members make less errors by rejecting bad alternative.